Α- & β-crystalline phases in polyvinylidene fluoride as tribo-piezo active layer for nanoenergy harvester. (September 2019) - Rajeev, Sreenidhi Prabha; Sabarinath, S; Subash, CK; Valiyaneerilakkal, Uvais; Parameswaran, Pattiyil; Varghese, Soney
The manuscript introduces the use of non-electrically polled spin-coated thin polyvinylidene fluoride (PVDF) films as the active layers in a contact electrification-based nanoenergy harvester. The four-layered device utilizes both piezo and triboelectric effect coupled with electrostatic induction. The elucidation of potential generation during contact between crystalline phases ( α and β ) of PVDF layer material is investigated in the manuscript. Fourier transform infrared–attenuated total reflectance spectroscopy is carried out to illustrate the α - and β -phases in PVDF pellet, prepared film as well as the film after contact. Dynamic contact mode electrostatic force microscopy (DC-EFM) along with atomic force microscopy is used for the evaluation of reverse piezoelectric, local ferroelectric, triboelectric voltage and adhesive energy of the PVDF films before–after contact process. Quantum chemical calculation is performed using density functional theory to explain possible electron transitions in the active layers between the cylindrically symmetric α -phase and electrical double layer charges in the β -phase of PVDF. The interface study of the film is also carried out both experimentally using DC-EFM and through quantum chemical calculations. The fabricated device with the hybrid piezo-tribo layer promises to be a simple and low-cost energy source for the next-generation self-powered electronic devices. The device can also be used as knock sensor in engines as well as a capacitor.